Comparison of hepatitis b virus infection in HIV-infected and HIV-uninfected participants enrolled in a multinational clinical trial: HPTN 052 - Amy E. Greer (2018)
© 2017 Wolters Kluwer Health, Inc. All rights reserved. Objective: Data comparing hepatitis B virus (HBV) infection in HIV-infected [HIV(+)], and HIV-uninfected [HIV(2)] individuals recruited into the same study are limited. HBV infection status and chronic hepatitis B (cHB) were characterized in a multinational clinical trial: HIV Prevention Trials Network (HPTN 052). Method: HBV infection status at enrollment was compared between HIV(+) (N = 1241) and HIV(-) (N = 1232) from 7 HBV-endemic countries. Hepatitis B e antigen and plasma HBV DNA were determined in cHB. Median CD4, median plasma HIV RNA, and prevalence of transaminase elevation were compared in HIV(+) with and without cHB. Significance was assessed with x2Fisher exact and median tests. Results: Among all participants, 33.6% had HBV exposure without cHB (8.9% isolated HBV core antibody, "HBcAb"; 24.7% HBcAb and anti-HB surface antibody positive, "recovered"), 4.3% had cHB, 8.9% were vaccinated, and 53.5% were uninfected. Data were similar among HIV(+) and HIV(2) except for isolated HBcAb, which was more prevalent in HIV(+) than HIV(2) [10.1% vs. 7.7%, P = 0.046]. Median HBV DNA trended higher in HIV(+) than in HIV(2). In HIV (+) with cHB versus those without cHB, transaminase elevations were more prevalent (alanine aminotransferase # grade 2, 12% vs. 5.2%, P = 0.037; aspartate aminotransferase # grade 2, 26% vs. 6.0%, P, 0.001), CD4 trended lower, and HIV RNA was similar. Conclusions: HBV infection status did not differ by HIV infection status. HIV co-infection was associated with isolated HBcAb and a trend of increased HBV DNA. In HIV, cHB was associated with mild transaminase elevations and a trend toward lower CD4.